Training patterns and sports injuries in triathletes - Shaw, Therese; Howat, Peter; Maycock, Bruce; Trainor, M. (Sports Medicine Australia, 2004)
Sports-related injuries are a significant health problem within Australia, and constitute a national health priority. There is limited Australian research data available on factors that contribute to triathlon injuries, and in particular on how training patterns relate to injury risk. This study examined the association between training patterns and injury in mostly non-elite triathletes. A cross-sectional survey of 258 triathletes completed a questionnaire that focused on injuries they had sustained during the previous three triathlon seasons. Statistical associations were found between hours of training and sustaining an injury. These associations were U shaped, with those triathletes training at low levels and at high levels more likely to sustain an injury. The results suggest that, for non-elite triathletes, the likelihood of sustaining an injury is least when training for a total of 8 to 10 hrs per week, specifically cycling for five to six hrs and running for three to four hrs weekly. Time spent on swimming training does not appear to affect injury risk.This research is seen as a contribution towards assisting triathletes in the planning of training programs aimed at reducing the risk of injury.